Positional Hand Pallor and Isolated Epitrochlear Lymphadenitis Secondary to Bartonella henselae Infection. (Bangladesh Journal of Medical Science, 2021)
Cat scratch disease is a communicable disease caused by the Bartonella henselae bacteria. Regional lymphadenopathy is the hallmark of cat scratch disease and about 75% of lymphadenopathy cases are localized in the head and neck region. An epitrochlear lymphadenopathy is a rare condition at any age and often misdiagnosed as it is not normally palpable. External compression of an enlarged epitrochlear lymph node compromising vascularity was not mentioned in any literature before. We present a case of a 13-year-old girl with right positional ipsilateral hand pallor and epitrochlear lymphadenitis with serological evidence of Bartonella henselae infection.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.914-917